Ketahanan Fiskal: Studi Kasus Malaysia dan Indonesia - Jaka Sriyana (Economic Journal of Emerging Markets, 2005)
In the last ten years, fiscal policy has played an important role to the macroeco¬nomy. This paper aims to explore the fiscal strength and the synchronization between fiscal and monetary policy for Malaysia and Indonesia. For the first issue, this paper applies the Trehan and Walsh method, meanwhile the Berument’s approach is used to examine the syn¬chronization between fiscal and monetary policy. The result shows that in case of Malaysia, the government applied tax-financed policy; meanwhile Indonesia has entered to the debt trap. The Malaysia’s government has also synchronized fiscal and monetary policy, which is different with that in Indonesia.Keyword: Fiscal policy, tax-financed policy, debt trap.